Root trait variation and its contribution to drought tolerance in bambara groundnut (Vigna subterranea (L.) Verdc.) - Mateva, Kumbirai Ivyne (2022)
Bambara groundnut (Vigna subterranea (L) Verdc), is an exemplar neglected African grain legume that thrives under strikingly contrasted environments relative to other grain legumes. Originating in West Africa, its distribution spans across aridity gradients from tropical dry climates in Senegal and Kenya, respectively, down to arid and semi-arid regions in sub-Saharan Africa. This is on soils more or less poor in nutrients and formed under variable pedoclimatic conditions. In these contrasting habitats, it is generally agreed that bambara groundnut has diversified due to domestication from its wild relative, Vigna subterranea var. spontanea (Harms) Hepper, as a result of steady changes through natural and artificial selection. Bambara groundnut is a close relative of cowpea (Vigna unguiculata) and morphologically fits into the same niche as groundnut (Arachis hypogaea L.). The wide distribution in natural environments and ability to tolerate both biotic and abiotic stresses better than cowpea and groundnut, make bambara groundnut an interesting model for examining diversification in response to ephemeral soil water resources. Although important, comprehensive variation assessment on below ground (root) traits in bambara groundnut have not been pursued. The hypothesis was that by focusing on naturally occurring genotypic variation in root system architecture and rooting distribution, bambara groundnut genotypes from dry agroecologies with periodic drought stress had developed root system traits that improved water foraging in deeper soil depths over time. This could be visualised and quantified using a low-cost polyvinyl chloride column (PVC) phenotyping system and image analysis.